2015
DOI: 10.1109/tpel.2015.2440914
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Charging via Multimode Resonant Cavity Enabled Wireless Power Transfer

Abstract: The majority of existing wireless power solutions are capable of 2-Dimensional surface charging of one or two devices, but are not well suited to deliver power efficiently to large numbers of devices placed throughout a large 3-Dimensional volume of space. In this work we propose an unexplored type of wireless power transfer system based on electromagnetic cavity resonance. Here we use the natural electromagnetic modes of hollow metallic structures to produce uniform magnetic fields which can simultaneously po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“…For the muti-moded cavity case, however, the modes are very close to one another such that in the vicinity of a given mode, the effect of other nearby modes can widely vary and more terms in the Taylor's series need to be retained. Additionally for an accurate construction of the circuit representation (7) and (8), the identification process must be repeated for all excited modes. To overcome the challenges of the traditional identification approach, we apply a different identification procedure that relies on fitting the frequency domain Z 21 to a rational function such that, in the vicinity of a given mode frequency, it behaves much like (8).…”
Section: A Identification Of Modes Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the muti-moded cavity case, however, the modes are very close to one another such that in the vicinity of a given mode, the effect of other nearby modes can widely vary and more terms in the Taylor's series need to be retained. Additionally for an accurate construction of the circuit representation (7) and (8), the identification process must be repeated for all excited modes. To overcome the challenges of the traditional identification approach, we apply a different identification procedure that relies on fitting the frequency domain Z 21 to a rational function such that, in the vicinity of a given mode frequency, it behaves much like (8).…”
Section: A Identification Of Modes Dynamicsmentioning
confidence: 99%
“…It is worth noting that although the circuit model relies on the terminal characteristics, the modal decomposition of equations (7) and (8) allow the symmetrical nature of the modes to be determined as exhibited by the sign of r 21 . Furthermore, the different RLC resonators represent the coupled modes resulting from the interaction of the DRs with the SCR modes.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a group from Massachusetts Institute of Technology(MIT) demonstrated that WPT efficiency can be enhanced via resonant coupling [3]. Since then, after years of development, many scientific researchers have been attracted to this concept [8][9][10][11][12][13]. Several solutions based on various types of resonators have been proposed to deal with the most pressing problems of improving efficiency and transmission distance, and meaningful results were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional Tx coil structure is investigated for the maximum power transfer to single dynamic Rx irrespective of the orientation [21,22]. However, the uniform power distribution to multiple Rx with three-dimensional structure is difficult to control and requires additional control circuitry at the Tx coil.…”
Section: Introductionmentioning
confidence: 99%